1994
DOI: 10.1111/j.1745-6584.1994.tb00641.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative Importance of Baseflow and Quickflow from Hydrographs of Karst Spring

Abstract: Evaluation of recession hydrographs, from four karst springs in Europe, provides important information concerning the flow process operating in karst aquifer systems. Three analytic equations are used to evaluate the hydrographs: Mangin's equation, that assumes the recession is composed of both quickflow and baseflow; Coutagne's equation which considers the recession to be the response of a single reservoir; and a new function, Ht (which is derived from Coutagne's equation), that refers to the whole recession … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
129
0
8

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(138 citation statements)
references
References 15 publications
1
129
0
8
Order By: Relevance
“…Figure 3 shows that the autocorrelation coefficients of daily discharges reach a value of 0.2 in 63 days and a null value in 114 days. This can be explained by a strong memory effect of the aquifer (Mangin, 1984;Larocque et al, 1998) and the predominance of baseflow component (Padilla et al, 1994;Pulido-Bosch et al, 1995, 1999Cerôn et al, 1999). Figure 4 shows autocorrelation coefficients of monthly discharges of the Gradole Spring and monthly precipitation that fell on the catchment in the period from January 1987 to December 1998.…”
Section: Basic Characteristic Of the Gradole Spring And Catchmentmentioning
confidence: 99%
“…Figure 3 shows that the autocorrelation coefficients of daily discharges reach a value of 0.2 in 63 days and a null value in 114 days. This can be explained by a strong memory effect of the aquifer (Mangin, 1984;Larocque et al, 1998) and the predominance of baseflow component (Padilla et al, 1994;Pulido-Bosch et al, 1995, 1999Cerôn et al, 1999). Figure 4 shows autocorrelation coefficients of monthly discharges of the Gradole Spring and monthly precipitation that fell on the catchment in the period from January 1987 to December 1998.…”
Section: Basic Characteristic Of the Gradole Spring And Catchmentmentioning
confidence: 99%
“…That is why several regimes are considered in the discharge process. Padilla et al (1994) suggested that the discharge in karstic systems is represented by two components: one linear, described by the Maillet formula associated with the recession of the saturated zone; and the other, non-linear, referred by a homographic formula related to the non-saturated zone. Malik (2015) implemented an iterative solution of several exponential and linear relationships for the hydrograph separation.…”
Section: Discussionmentioning
confidence: 99%
“…Many complex 311 functions have been developed in this context, for example to explain the outflow from karstic 312 aquifers (Padilla et al, 1994), channel banks , surface depressions 313 such as lakes or wetlands (Griffiths and Clausen, 1997), etc., but many other recession flow models 314 assume a linear relationship between storage and outflow, described by the classic exponential 315 decay function of :…”
Section: Spring Base Flows and Aquifer Recharge 306mentioning
confidence: 99%